The influence of genotype, sex, and dietary lysine on carcass quality characteristics of 230 and 280 lb finishing pigs - S R Stuewe; K G Friesen; Jim L Nelssen; Robert D Goodband; Michael D Tokach; John A Unruh (Kansas Agricultural Experiment Station Research Reports, 1992)
When pigs were fed to 230 Ib, high-lean genotype loin eyes had less visual marbling and a higher saturation index (more vivid or intense color) than medium-lean genotype loin eyes. Loin eye chops from high-lean gilts had greater cooking losses and WarnerBratzler shear values (mechanically tougher) than those from high-lean barrows and medium-lean barrows and gilts. When pigs were fed to 280 Ib, medium-lean genotype loin eyes had a lighter color visually and indicated by Hunter L* values, more marbling, less firmness, more moisture exudate, and a higher chop thaw loss than high-lean loin eyes. Barrow loin eyes had more marbling and less thaw loss than gilt loin eyes. Loin eye chops from high-lean barrows had higher Warner-Bratzler shear values than high-lean gilts and medium-lean barrows and gilts. Dietary lysine levels had minimal effects on carcass Quality for pigs fed to either 230 or 280 lb.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Pork quality; Lysine; Sex; Genotypes